Baltar, Rosalía (2012): Letrados en tiempos de Rosas. Mar del Plata: EUDEM; 250 pp. - Vanina Edith Rodríguez (Verba Hispanica, 2014)
Baltar, Rosalía (2012): Letrados en tiempos de Rosas. Mar del Plata: EUDEM; 250 pp.